Changes in Body Mass Related to the Initiation of Disease‐Modifying Therapies in Rheumatoid Arthritis. Issue 8 (27th July 2016) - Baker, Joshua F.; Sauer, Brian C.; Cannon, Grant W.; Teng, Chia‐Chen; Michaud, Kaleb; Ibrahim, Said; Jorgenson, Erik; Davis, Lisa; Caplan, Liron; Cannella, Amy; Mikuls, Ted R.
Abstract : Objective: Unintentional weight loss is important and can be predictive of long‐term outcomes in patients with rheumatoid arthritis (RA). This study was undertaken to assess how primary therapies for RA may influence changes in body mass index (BMI) in RA patients from a large administrative database. Methods: Unique dispensing episodes of methotrexate, prednisone, leflunomide, and tumor necrosis factor inhibitors (TNFi) administered to RA patients were identified from the US Department of Veterans Affairs pharmacy databases. Values for C‐reactive protein (CRP) level and BMI closest to the time point within 30 days of the treatment course start date and at follow‐up time points were linked. Missing laboratory values were imputed. Weight loss was defined as a decrease in BMI of >1 kg/m 2 . Regression models were used to evaluate changes in BMI during each drug treatment as compared to treatment with methotrexate. To assess the impact of confounding by indication, propensity scores for use of each drug were incorporated in analyses using matched‐weighting techniques. Results: In total, 52, 662 treatment courses in 32, 859 RA patients were identified. At 6 months from the date of prescription fill, weight gain was seen among patients taking methotrexate, those taking prednisone, and those taking TNFi. On average, compared to methotrexate‐treated patients, prednisone‐treated patients had significantly more weight gain, while leflunomide‐treated patients demonstrated weight loss. In multivariable models, more weight loss (β = −0.41 kg/m 2, 95% confidence interval [95% CI] −0.46, −0.36; P  < 0.001) and a greater risk of weight loss (odds ratio 1.73, 95% CI 1.55, 1.79; P  < 0.001) were evident among those receiving leflunomide compared to those receiving methotrexate. Treatment with prednisone was associated with greater weight gain (β = 0.072 kg/m 2, 95% CI 0.042, 0.10; P  < 0.001). These associations persisted in analyses adjusted for propensity scores and in sensitivity analyses. Conclusion: Leflunomide is associated with significantly more, but modest, weight loss, while prednisone is associated with greater weight gain compared to other therapies for RA.